2010
DOI: 10.1111/j.1365-2893.2009.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effectiveness and cost-effectiveness of antiviral treatment in hepatitis C

Abstract: We systematically reviewed the evidence for long-term effectiveness and cost-effectiveness of antiviral treatment in patients with chronic hepatitis C. We performed a systematic literature search on the long-term effectiveness and cost-effectiveness of AVT in hepatitis C (1990-March 2007), and included health technology assessment (HTA) reports, systematic reviews, long-term clinical trials, economic studies conducted alongside clinical trials and decision-analytic modelling studies. All costs were converted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…33 These antiviral therapies, namely interferon or peg-interferon with ribavirin, have been shown to be reasonably cost-effective when used to prevent progression to AdvLD as a single treatment cycle of 24 or 48 weeks. 34 Specifically, costs per quality adjusted life year (QALY) when compared with no treatment are generally estimated to fall below cost effectiveness thresholds (e.g., < £30,000 per QALY or < U.S.$50,000 per QALY), although one study found that antiviral treatment may not be cost-effective in patients with genotype 1 who have progressed to cirrhosis. [34][35][36][37] In the present study, HCV-related antiviral therapy costs (e.g., interferon α-2a and α-2b, interferon alphacon a, pegylated interferon α-2a and α-2b, and ribavirin), represented a large component of drug costs for HCV patients without AdvLD or with compensated cirrhosis, with PPPY costs for antiviral therapy of $2,445 and $3,243, respectively.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…33 These antiviral therapies, namely interferon or peg-interferon with ribavirin, have been shown to be reasonably cost-effective when used to prevent progression to AdvLD as a single treatment cycle of 24 or 48 weeks. 34 Specifically, costs per quality adjusted life year (QALY) when compared with no treatment are generally estimated to fall below cost effectiveness thresholds (e.g., < £30,000 per QALY or < U.S.$50,000 per QALY), although one study found that antiviral treatment may not be cost-effective in patients with genotype 1 who have progressed to cirrhosis. [34][35][36][37] In the present study, HCV-related antiviral therapy costs (e.g., interferon α-2a and α-2b, interferon alphacon a, pegylated interferon α-2a and α-2b, and ribavirin), represented a large component of drug costs for HCV patients without AdvLD or with compensated cirrhosis, with PPPY costs for antiviral therapy of $2,445 and $3,243, respectively.…”
Section: ■■ Discussionmentioning
confidence: 99%
“…34 Specifically, costs per quality adjusted life year (QALY) when compared with no treatment are generally estimated to fall below cost effectiveness thresholds (e.g., < £30,000 per QALY or < U.S.$50,000 per QALY), although one study found that antiviral treatment may not be cost-effective in patients with genotype 1 who have progressed to cirrhosis. [34][35][36][37] In the present study, HCV-related antiviral therapy costs (e.g., interferon α-2a and α-2b, interferon alphacon a, pegylated interferon α-2a and α-2b, and ribavirin), represented a large component of drug costs for HCV patients without AdvLD or with compensated cirrhosis, with PPPY costs for antiviral therapy of $2,445 and $3,243, respectively. HCV antiviral PPPY costs for HCC and transplant patients were less at $1,599 and $1,653, respectively, which represents a smaller proportion of both overall drug costs and incremental drug costs between HCC and transplant patients and their matched comparison enrollees.…”
Section: ■■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are partly due to the slow progression of HCV infection to cirrhosis, especially for women [18], and the relatively high costs for patients treated with new protease inhibitors (boceprevir and telaprevir). However, standard of care treatment is estimated in the literature to be cost-effective in treatment-naïve patients [19]. Therefore we also estimated the ICER when standard of care treatment is used (scenarios 2a and 2b) and found a more favourable ICER than when new treatment options are used, but still above the certain cost-effective threshold of J20,000.…”
Section: Discussionmentioning
confidence: 94%
“…Reduction in viral load is another relevant activity of interferons. In combination with ribavidin, interferon- prolongs survival in patients with hepatitis C [26,27]. Flu-like syndrome, malaise, neuropsychiatric disorders, hematologic and liver toxicity are the most common doselimiting side-effects.…”
Section: Interferon-mentioning
confidence: 99%